2023
DOI: 10.1128/spectrum.00174-23
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Analysis of the pks Gene in Clinical Klebsiella pneumoniae Isolates

Abstract: The infection rate with pks -positive K. pneumoniae has been increasing in recent years. Two previous surveys in Taiwan reported 25.6% pks gene islands and 16.7% pks -positive K. pneumoniae strains in bloodstream infections, and Chinese scholars also did a survey of K. pneumoniae bloodstream infections in Changsha, China, and found 26.8% pks -po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, this explanation does not fully account for the increased proteins from the fim operon, indicating the involvement of broader regulatory mechanisms. A recent study has reported a direct correlation between biofilm formation and the colibactin operon in isolates of E. coli and K. pneumoniae 71,72 . Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin 73 , it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway.…”
Section: Discussionmentioning
confidence: 98%
“…However, this explanation does not fully account for the increased proteins from the fim operon, indicating the involvement of broader regulatory mechanisms. A recent study has reported a direct correlation between biofilm formation and the colibactin operon in isolates of E. coli and K. pneumoniae 71,72 . Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin 73 , it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway.…”
Section: Discussionmentioning
confidence: 98%
“…coli and K. pneumoniae. , Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin, it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway. Recently, a phenotypic switch between type III fimbriae and the hypermucoviscous capsule in response to iron levels has been reported in the SGH10 strain. , The iron-regulated outer membrane protein IroP, encoded in the virulence plasmid, inhibits the expression of the mrk operon under low iron conditions, inhibiting biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…30 Recently, surveys from different areas indicated that the infection of colibactin-producing K. pneumoniae (pks-positive K. pneumoniae) was scaled up rapidly. 31 A patient encountered recurrent infections with CG23-I hvKP. The isolates all have colibactin genes; one of the isolates, with duplication of the initiator tRNAfMet gene, grew faster in a poor nutritional environment and exhibited enhanced virulence.…”
Section: Colibactinmentioning
confidence: 99%